Experimental evaluation on heat transfer limits of sodium heat pipe with screen mesh for nuclear reactor system. (5th June 2022) - Tian, Zhixing; Zhang, Jiarui; Wang, Chenglong; Guo, Kailun; Liu, Yu; Zhang, Dalin; Tian, Wenxi; Qiu, Suizheng; Su, G.H.
Highlights: Wall and vapor temperature of heat pipes are measured. Capillary limits are characterized experimentally and are predicted by the model of Chi under horizontal condition. Sonic limits are characterized and occur during the frozen startup process. A model of entrainment limit is proposed and verified by the experiments. Transition temperature of vapor is measured experimentally and is affected by the inclination angle. Abstract: Heat pipe cooled reactor (HPR) is an ideal technology and a potential future niche where reliability and simplicity are key requirements. The heat transfer capacity of heat pipes determines the application range of HPR. Heat transfer limits (HTLs) of heat pipes are investigated, and the models of HTLs are evaluated in this study. Various HTLs of heat pipes with different filling ratios are tested. For the capillary limit, there is a sudden dryout in the evaporator section, in which the model of Chi is applicable for the horizontal conditions with a deviation of 19.0% but not for the inclined conditions. There is a possibility of sonic limit for a temperature rise in the adiabatic and condenser sections. The sonic limit predicted by Levy model is always higher than the experimental results. The entrainment limit is accompanied by a sudden rise in temperature of the evaporator section and temperature fluctuation in the condenser section, which can be estimated by using the wave-induced model with a relative error of 45.3% and is affected by the wick and inclination angle. The Knudsen number is used to determine the vapor state and the recommended critical Knudsen number of 0.01 is less than experimental data, which neglects the effect of inclination angle. The experimental results provide references for the heat pipe design and the accuracy of the present models are estimated.